Pretreatment of Donor Islets With the Na+/Ca2+ Exchanger Inhibitor Improves the Efficiency of Islet Transplantation. Issue 8 (7th June 2013) - Mera, T.; Itoh, T.; Kita, S.; Kodama, S.; Kojima, D.; Nishinakamura, H.; Okamoto, K.; Ohkura, M.; Nakai, J.; Iyoda, T.; Iwamoto, T.; Matsuda, T.; et al.
Abstract: Pancreatic islet transplantation is an attractive therapy for the treatment of insulin‐dependent diabetes mellitus. However, the low efficiency of this procedure necessitating sequential transplantations of islets with the use of 2–3 donors for a single recipient, mainly due to the early loss of transplanted islets, hampers its clinical application. Previously, we have shown in mice that a large amount of HMGB1 is released from islets soon after their transplantation and that this triggers innate immune rejection with activation of DC, NKT cells and neutrophils to produce IFN‐γ, ultimately leading to the early loss of transplanted islets. Thus, HMGB1 release plays an initial pivotal role in this process; however, its mechanism remains unclear. Here we demonstrate that release of HMGB1 from transplanted islets is due to hypoxic damage resulting from Ca 2+ influx into β cells through the Na + /Ca 2+ exchanger (NCX). Moreover, the hypoxia‐induced β cell damage was prevented by pretreatment with an NCX‐specific inhibitor prior to transplantation, resulting in protection and long‐term survival of transplanted mouse and human islets when grafted into mice. These findings suggest a novel strategy with potentially great impact to improve the efficiency of islet transplantation in clinical settings by targeting donor islets rather than recipients. Abstract : The early loss of transplanted mouse and human islets is prevented by the pretreatment of donor islets with the Na + /Ca2 + exchanger inhibitor in mice.